Influence of the supplementary reinforcement on the shear strength of beams with prefabricated truss stirrups - Rosângela Silva Pinto; Vanessa Carolaine Sousa; Luamim Sales Tapajós; Maurício de Pina Ferreira; Aarão Ferreira Lima Neto (Revista IBRACON de Estruturas e Materiais, 2021)
abstract: This paper presents the results of seven experimental tests in reinforced concrete wide beams, aiming to investigate their performance when subjected to shear, using prefabricated truss stirrups as shear reinforcement, as well as a supplementary reinforcement to control cracks by delamination. The main analysed variables were: position of the supplementary reinforcement, inclination of the shear reinforcement, and spacing between stirrups. Results showed that strength increments of up to 142% were obtained using the prefabricated truss stirrups. Furthermore, the experimental results were compared with the theoretical shear strength estimates of the tested beams, following the recommendations of NBR 6118 (2014), Eurocode 2 (2004), and ACI 318 (2014), in order to evaluate the safety level of these codes when designing concrete elements subjected to shear with the reinforcement used in this paper.